Identification of workers with past asbestos exposure in Tuscany eligible to health surveillance programme - Chellini, Elisabetta; Lippi, Giuseppe; Festa, Gianluca; Fani, Sandra; Capacci, Fabio; Martini, Andrea; Battisti, Francesca (La Medicina del Lavoro, 2019)
Background: In 2016 the Administration of the Tuscany Region, Italy, established a health surveillance programme for workers with past asbestos exposure. The programme includes two levels of activities, a local basic health evaluation, and a centralized in-depth evaluation of specific cases. Objectives: To estimate the number and identify the workers with past exposure to asbestos in Tuscan industrial settings entitled to participate in the health surveillance programme. Methods: The number of formerly-exposed workers was estimated from the records of the working population of 15,441 workers of thirteen Tuscan asbestos industrial plants and from the existing data bases of the Local Health Administrations (USLs) and the Institute for Study, Prevention and Cancer Network (ISPRO), and from national data bases such as Social Security Administration (INPS) and National Institute for Insurance against Accidents at Work (INAIL). The expected number of medical examinations per year was estimated from the adhesion rates seen in previous comparable programmes. Results: The estimated number of workers with past asbestos exposure eligible to the programme was 5,446. The estimated number of health examinations in the first and second phases of the surveillance programme during 2016-24 was 7,275 and 7,155, respectively, follow-up examinations included. The number of workers identified from local data bases was 4,713: They had been operating in 129 plants that had been using asbestos in the past. Further 1,395 workers were identified from previous health surveillance activities. Conclusions: The use of several sources of information and the cooperation between occupational health services made it possible to identify a high proportion of former asbestos workers and plants., It is, nevertheless, still necessary to complete the list of eligible workers, and to facilitate their participation by making the programme more widely known.